Prevalence and Treatment Needs for Early Childhood Caries Among 3–5-Year-Old Children From a Rural Community in Uganda - Musinguzi, Norman; Kemoli, Arthur; Okullo, Isaac (Frontiers in Public Health, 2019)
Introduction: Early Childhood caries (ECC) is the term used to describe dental caries in children aged 71 months and below. ECC causes a lot of pain and discomfort in the affected children and is expensive to treat. There is limited data on the prevalence of ECC in preschool children resident in the rural Uganda. Aim: To determine the prevalence and treatment needs for ECC among 3–5-year-old nursery school children in a rural community in Rukungiri District, Uganda. Study Design: This was a descriptive cross-sectional study in which 432 nursery school children aged 3–5 years from rural Nyakagyeme sub-county in Ugandan, participated. Informed consent for participation in the study by the children was obtained from their parents/guardians prior to the commencement of the study. The examination of the participants was done under field conditions, with the child lying his or her back of the neck on the PI's lap, with both of them seated on a bench and using natural light augmented with a headlamp to examine the oral cavity. The findings of the examination were recorded on individualized modified WHO Oral Health Assessment Forms for children. Data Analysis: The data gathered were analyzed using Windows SPSS Version 23.0 computer programme, and descriptive results for the variables obtained and Mann Whitney and Kruskal–Wallis tests used to compare and relate the variables. The P<0.05 was considered statistically significant with the Confidence interval set at 95%. The findings were presented in Tables and Figures. Results: A total of 230 (53.2%) male and 202 (46.6%) female participants, with 118 (27.3%), 145 (33.6%), 169 (39.1%) aged 3, 4, and 5 years old respectively, participated in the study. The overall prevalence of dental caries among the participants was 48.6%, with 11.6%, 18.5% and 18.5% recorded for the 3-, 4-, and 5-year old children, respectively. The male participants had a higher prevalence (26.1%) than the female counterparts (22.5%). The mean “dmft” for the participants was 2.04 (SD = 3.01) with the decay component (dt) having the highest value (M = 1.97, SD = 2.89), and contributing to 88.6% of the dental caries experience. The mean “dmft” was 1.79, 2.37 and 1.91 for the 3-, 4-, and 5-year old children, respectively, and the difference in the mean “dmft” among the age groups was not statistically significant. Conclusion: The prevalence of ECC of 48.6% was moderate in this study population. The high level of unmet treatment need as exemplified by the high dental caries experience, was a cause for concern as this forms a risk factor for caries in the permanent dentition.